Effect of forage quality and narasin inclusion on ruminal fermentation, nutrient intake, and total tract digestibility of Nellore steers - de Paula, Matheus Felipe Freitas Viana; Marques, Rodrigo S.; Pires, Alexandre Vaz; Soares, Letícia Carolina Bortolanza; Limede, Arnaldo Cintra; Ferreira, Evandro Maia; Polizel, Daniel Montanher [UNESP] (Oxford University Press (OUP), 2024)
The study aimed to evaluate the effects of forage quality and narasin inclusion on intake, digestibility, and ruminal fermentation of Nellore steers. Twenty-eight rumen-cannulated Nellore steers (initial body weight [BW] = 350 ± 32.4 kg) were allocated to individual pens in a randomized complete block design, with 7 blocks, defined according to the fasting BW at the beginning of the experiment. The steers were randomly assigned within blocks to 1 of 4 experimental diets in 2 × 2 factorial arrangements, being the first-factor forage quality (MEDIUM = 81 g of CP/kg of dry matter [DM], and HIGH = 153 g of CP/kg of DM), and the second factor was the inclusion (N13 = diet plus 13 mg/kg of DM of narasin) or not (N0) of narasin (Zimprova; Elanco Animal Health, São Paulo, Brazil). The experiment consisted of a 28-d period with 22 d for adaptation and the last 6 d for data collection. No haylage quality × narasin interaction (P ≥ 0.68) was observed on DM and nutrient intake. Haylage quality affected (P ≤ 0.01) DM intake, with greater values observed for steers fed HIGH compared with MEDIUM haylage. There was an increase (P < 0.001) in OM, NDF, hemicellulose, and CP intake for steers consuming HIGH vs. MEDIUM haylage. Including N13 did not affect (P > 0.39) DM and nutrient intake of steers. No haylage quality × narasin interactions were detected (P ≥ 0.60) for total tract nutrient digestibility. However, steers fed with HIGH haylage showed an increase (P > 0.001) in DM and digestibility of all nutrients compared with MEDIUM. Steers fed a MEDIUM haylage had a greater (P < 0.01) proportion of acetate compared with steers fed HIGH during all evaluated hours. Steers fed HIGH haylage had a greater (P < 0.01) proportion of propionate at 0 h compared with steers consuming MEDIUM, whereas at 12 h, steers consuming MEDIUM hay had a greater (P < 0.01) proportion of propionate vs. HIGH haylage. A haylage quality × narasin and haylage quality × time of collection interactions were detected (P ≤ 0.03) for rumen ammonia concentration, which was reduced (P < 0.03) in N13 vs. N0 steers consuming HIGH haylage. Collectively, high-quality haylage allows increased consumption and digestibility, with more energy-efficient ruminal fermentation. In addition, narasin might be an important nutritional tool in forage-based diets to enhance the ruminal fermentation parameters of Bos indicus Nellore steers.
Keywords: feed additives; forage quality; ionophore; narasin; ruminal fermentation